Histatin 5 inhibits adhesion of C. albicans to Reconstructed Human Oral Epithelium - Moffa, Eduardo B.; Mussi, Maria C. M.; Xiao, Yizhi; Garrido, Saulo S.; Machado, Maria A. A. M.; Giampaolo, Eunice T.; Siqueira, Walter L. (Frontiers in Microbiology, 2015)
As a polymorphic species, C. albicans is capable of switching between yeast and hyphal forms. While the yeast form is most commonly associated with systemic disease, the hyphae are more adept at adhering to and penetrating host tissue and are therefore frequently observed in mucosal fungal infections, most commonly oral candidiasis. The objective of this study was to evaluate the potential of Histatin 5 to protect the Human Oral Epithelium against C. albicans adhesion. Human Oral Epithelial Tissues (HOET) were incubated with PBS containing histatin 5 for 2 h, followed by incubation with C. albicans for 1 h at 37 °C, after HOET were washed with PBS, transferred to fresh RPMI and incubated for 16 h at 37°C at 5 % CO2. HOET were then prepared for histopathological analysis using light microscopy. In addition, the TUNEL assay was employed to evaluate the apoptosis of epithelial cells using fluorescent microscopy. HOET pre-incubated with histatin-5 showed a lower rate of C. albicans growth and cell apoptosis when compared to the control groups. The data suggest that the coating with histatin-5 is able to reduce C. albicans colonization on epithelial cell surfaces and also protect the basal cell layers from undergoing apoptosis.